REKONSTRUKSI KONSEP MASLAHAH MURSALAH SEBAGAI BASIS IJTIHAD KONTEMPORER DALAM MENJAWAB TANTANGAN MODERNITAS - Abdul Gofar; Siti Amina; Nisrina Fajrin (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2025)
This study examines the strategic role of maslahah mursalah in contemporary ijtihād amid the complexities of modernity. Using a qualitative library-based approach, it explores the relevance of maslahah to emerging issues such as technology, human rights, and environmental challenges. The findings show that maslahah mursalah serves not only as a legal tool but also as an ethical framework aligned with maqāṣid al-sharīʿah, enabling Islamic law to respond adaptively to social change.